Does Self-Esteem Mediate the Relationship between Interpersonal Problems and Symptoms of Disordered Eating? - Lampard, Amy; Byrne, S.; McLean, N. (John Wiley & Sons Ltd., 2011)
It has been proposed that interpersonal problems play a role in the maintenance of disordered eating because of an adverse effect on self-esteem, which in turn encourages the pursuit of achievement in the valued domain of weight and shape. This study aimed to identify the types of interpersonal problems that are associated with disordered eating and to determine whether self-esteem mediates the relationship between interpersonal problems and eating disorder symptoms. Female university students (n = 227) completed the Inventory of Interpersonal Problems-32, Eating Disorder Examination Questionnaire and Rosenberg Self-Esteem Scale. Regression analysis identified two forms of interpersonal problems that were associated with disordered eating: difficulties being sociable and being too dependent on the opinion of others. Self-esteem mediated the relationship between interpersonal problems and over evaluation of weight and shape but did not mediate the relationship between interpersonal problems and dietary restraint.